Cetuximab monotherapy for relapsing high-grade mucoepidermoid carcinoma: A case report and review of the literature. (August 2020) - Wu, Yubin; Han, Ling; Sheng, Yang; Wu, Shihai
Highlights: We report a case of recurrent high-grade MEC treated effectively with cetuximab. Cetuximab monotherapy may be a good option for patients with EGFR over expression. We reviewed some of the literature on cetuximab and MEC.